Dynamic Modelling Analysis of Vibrio sp. and Plankton Abundance in Intensive Shrimp Pond - Ariadi, Heri; Mujtahidah, Tholibah; Tartila, Shobrina Silmi Qori; Azril, Muh.; Ayisi, Christian Larbi (Universitas Negeri Semarang, 2024)
Vibrio sp. and plankton are important microorganisms in shrimp pond ecosystems. The research aims to predict the dynamics of Vibrio sp. and plankton abundance in intensive shrimp pond ecosystems based on causal model analysis. The research method used is an ex-pose facto causal design concept with quantitative descriptive data analysis using causal dynamic modeling. The results showed the water quality in the pond has a high correlation, except Vibrio sp. and alkalinity. In the pond ecosystem 24 genus of plankton from 6 classes. Chlorella sp. is the dominant plankton genus with an abundance of 1.00E+05-4.00E+05 cells/ml. Vibrio sp. abundance in ponds ranged from 1.38E+03 - 1.31E+05 CFU/ml. Based on the results of dynamic modelling, the growth pattern of Vibrio sp. lasted for 30 weeks which was divided into 4 growth phases. The conclusion of this study is that Vibrio sp. will dynamically experience a pure growth rate for 30 weeks with details of the initial growth phase (1-7 weeks), logarithmic growth phase (8-14 weeks), exponential phase (15-21 weeks), and growth declination phase (22-30 weeks). The growth phase of Vibrio sp. has a high degree of similarity to the growth pattern of plankton in the pond water ecosystem correlatively. The novelty of this research lies in the discovery of an estimation model for the abundance of Vibrio sp. and plankton during the shrimp farming cycle. This finding can serve as a fundamental reference for farmers to optimize feeding processes and conduct regular siphoning during the peak abundance of Vibrio sp. and plankton.